Naming Games After Cities: Learning from Modern Board Game Design for Game-Based Planning Approaches - Micael da Silva e Sousa (Urban Science, 2025)
City-building games are very popular, on both digital and analog platforms. However, analog games named after cities are a tradition in modern board games. These games, resulting from the game design innovations of the last decades, are engaging a growing number of players worldwide. We wanted to understand what drives players and game designers to develop games that have a direct connection with cities or urban matters. We intend to explore them and identify their design patterns in order to support game-based planning support tools, mostly for participatory and collaborative planning. Planners have been using game-based processes, and analog games seem to be the easier solution. We analyzed the top-ranking city-building games (CBGs) and games named after cities (GNACs) from Board Game Geek (BGG) and then ran a survey with BGG users (n = 102). The results show that GNACs do not deeply portray cities but tend to focus on a specific dimension. CBGs are better at mimicking an urban planning process but with many simplifications. Despite this, mastering the design of these two types of games is useful for planners who wish to use game-based planning processes. However, the engagement level might depend on the target audience.